Investigating the Mediating Role of Negative Repetitive Thoughts in the Relationship Between Behavioral Brain Systems and Sleep Quality With Mental Fatigue in Women With Type 2 Diabetes - Talaei Kahjugh, Mohammad; Nikmanesh, Arash; Pourmohammad Ghouchani, Kamran (Psychology of Woman Journal, 2025)
Objective: The present study aimed to determine the mediating role of negative repetitive thoughts in the relationship between behavioral brain systems and sleep quality with mental fatigue in women with type 2 diabetes.Materials and Methods: This study was a correlational design using structural equation modeling. The statistical population included all women with type 2 diabetes who were members of the Diabetes Patients Support Association in Tehran Province in 2025. A total of 265 women were selected as the research sample through convenience sampling. The instruments used in this study included the Negative Repetitive Thoughts Questionnaire (McEvoy, Mahoney, & Moulds, 2012), the Behavioral Inhibition/Activation Systems Scale (Carver & White, 1994), the Pittsburgh Sleep Quality Index (Buysse et al., 1989), and the Mental Fatigue Questionnaire (Smets, 1996). The data were analyzed using path analysis.Findings: The results showed that there was a significant and positive relationship between behavioral brain systems and sleep quality with mental fatigue through the mediation of negative repetitive thoughts. However, negative repetitive thoughts did not play a significant mediating role in the relationship between the behavioral activation system and mental fatigue.Conclusion: Our findings suggest that negative repetitive thoughts, behavioral brain systems, and sleep quality can be considered fundamental constructs in chronic illnesses such as type 2 diabetes. It can be concluded that these mechanisms may play a critical role in the persistence of the disease, and considering these relationships could be beneficial for the etiology and treatment of individuals with type 2 diabetes.